EXISTENCE OF KHIYAR IN ONLINE TRANSACTIONS (E COMMERCE) (COMPILATION OF SHARIAH ECONOMIC LAW) - Fauziah, Fauziah; Fathimah, Ema (Nurani, 2020)
Along with the development of culture and technology, selling and buying of goods was in the form of exchange of one item for another, and the medium of transaction is by using money and the sellers and buyers meet in one assembly or face to face. However, with current technological developments, transactions are no longer face to face or meet in one place. With the internet network, transactions are easily carried out. One of the phenomena of transactions in the economic field is the selling and buying transactions using electronic media. This is called online transactions or e-commerce, which is transactions carried out through internet services and internet technology. Since the two parties do not meet and face to face in this online transaction, it is very prone to fraud or cheating between the two. Based on this background, the researcher is interested in examining the Compilation of Sharia Economic Law that governs the concept of khiyar which is then applied to e-commerce. The results of this study indicate that khiyar stipulated in the Compilation of Sharia Economic Law is the khiyarof condition, in which the sellers and buyers may specify the terms of the transaction, which is for 3 days. Khiyarnaqdi, in practice, is a deferred payment. In khiyarru’yah, one of the parties when shopping online may first look at pictures presented by the online store. In khiyar ‘aib, there isa suffrage of the goods, so that when the goods have been received and there isa defect in the goods, it may be cancelled or continued. And the last is khiyarghabn and taghrib, which is the suffrage when finding something wrong about the quality of the goods sold if it does not in accordance with the picture or explanation of the sellers. Keywords: Khiyar, e-commerce, Compilation of Sharia Economic Law.